Phase I/II intra-patient dose escalation study of vorinostat in children with relapsed solid tumor, lymphoma, or leukemia - Tilburg, Cornelis M. van; Milde, Till; Witt, Ruth; Ecker, Jonas; Hielscher, Thomas; Seitz, Angelika; Schenk, Jens-Peter; Buhl, Juliane; Riehl, Dennis; Frühwald, Michael; Pekrun, Arnulf; Rössig, Claudia; et al. (Clinical epigenetics, 2019)
Until today, adult and pediatric clinical trials investigating single-agent or combinatorial HDAC inhibitors including vorinostat in solid tumors have largely failed to demonstrate efficacy. These results may in part be explained by data from preclinical models showing significant activity only at higher concentrations compared to those achieved with current dosing regimens. In the current pediatric trial, we applied an intra-patient dose escalation design.
Gesehen am 20.05.2020